Murder at the White Palace - Montclair, Allison (Montclair, Allison. Sparks & Bainbridge mystery, 2024)
"In post-WWII London, the matchmakers of The Right Sort Marriage Bureau are involved in yet another murder. In the immediate post-war days of London, two unlikely partners have undertaken an even more unlikely, if necessary, business venture--The Right Sort Marriage Bureau. The two partners are Miss Iris Sparks, a woman with a dangerous--and never discussed--past in British intelligence and Mrs. Gwendolyn Bainbridge, a genteel war widow with a young son entangled in a complicated aristocratic family. Looking to throw a New Year's Eve soiree for their clients, Sparks and Bainbridge scout an empty building--only to find a body contained in the walls. What they initially assume is a victim of the recent Blitz is uncovered instead to be a murder victim--stabbed several times. To make matters worse, the owner of the building is Sparks' beau, Archie Spelling, who has ties to a variety of enterprises on the right and wrong sides of the law, and the main investigator for the police is her ex-fiancée. Gwen, too, is dealing with her own complicated love life, as she tentatively steps back into the dating pool for the first time since her husband's death. Murder is not something they want to add to their plates, but the murderer may be closer to home than is comfortable, and they must do all they can to protect their clients, their business and themselves"--